The Business of Software: How We Build Things...and why things are 90% complete. - Armour, Phillip G. (Communications of the ACM, 2013)
The article presents the author's views on the process of computer software development, with information on the views of project managers in the software business. Topics include the knowledge discovery activity of systems development, information on the completion of tasks in the computer programming profession, and charts with mathematical equations on production and progress estimation.